Pemanfataan Tepung Jagaq ( Setaria italica) Sebagai Subsitusi Tepung Tapioka Terhadap Kualitas Fisik dan Organoleptik Bakso Sapi (Jurnal Peternakan Lingkungan Tropis, 2024)
The study  was conducted to determine the effects of Jagaq (Setaria italica) flour filler as a substitute for tapioca flour on the physical and organoleptic quality of beef meatballs. The parameters measured include water holding capacity test, pH test, mass loss test, texture test using a texture analyzer, and color test using the Hunter Lab Colorimeter test tool. Organoleptic quality includes the hedonic scale and hedonic qualities of color, flavor, texture, tenderness, and taste. This research was conducted at the Faculty of Agriculture, Mulawarman University in September 2023. The research experiment used a Completely Randomized Design (CRD) with five treatments with five replications.. The results of research on physical tests showed that beef meatballs with the addition of Jagaq flour had a significant effect (P
Keywords: Array; Array; Array; Array